Pemanfaatan Teknologi Energi Surya di Tumbang Datu - Matius sau; Rombe Rombe (DEDIKASI, 2018)
The purpose of community service activities through the PKM program is to help, motivate, train andassist Partners of the Karuaya Dance Group and the Carving Back Art Group in Lembang Tumbang Datu whoseefforts have not been economically productive, but have a strong passion and enthusiasm to work to make theirbusiness especially successful dance and carving art of Tana Toraja. The life of partners with the community is verylagging behind various aspects of life compared to the people in the surrounding area. The majority of the partnergroups dropped out of school, many did not graduate from high school, so they did not have the knowledge, abilitiesand skills to develop their businesses in utilizing and managing the tourism potential so large around them. Todevelop the business and standard of living of partners and surrounding communities, they are in dire need ofmentoring, training and touching the technology of solar power plants as a source of electrical energy lighting,sound systems, charge mobile phones and other productive activities so that they can develop their talents and notthink of funds for electricity payments because solar electricity is free. The specific target of the CommunityPartnership (PKM) program is to carry out development services utilizing dance and sculpture and art opportunitiesas a source of income for partners and surrounding communities; Maintenance training for solar power plants atpartner locations; Produce solar cell products that can convert solar energy into electrical energy.